Behavioural mimicry and loneliness in borderline personality disorder - Hauschild, Sophie; Winter, Dorina; Thome, Janine; Liebke, Lisa; Schmahl, Christian; Bohus, Martin; Lis, Stefanie (Comprehensive psychiatry, 2018)
Introduction - Interpersonal problems together with feelings of intense loneliness constitute a core symptom domain in borderline personality disorder (BPD). Mimicry is one social behaviour that serves the forming of social affiliation and building a sense of belonging. In the present study, we investigated whether behavioural mimicry is altered in BPD and whether it is linked to the patient's feeling of loneliness. - Methods - Individuals with BPD (N=26) and healthy participants (HC, N=25) performed a finger tapping task with a congruent or incongruent finger movement displayed preceding the presentation of the task relevant stimulus. Additional trials showing an immobile hand were used as a control condition. Mimicry strength was estimated as response facilitation after congruent and response interference after incongruent cues. - Results - Both HC and BPD patients showed facilitated responses after congruent finger movements. Only BPD patients exhibited interference by incongruent cues. The lonelier the BPD patients felt, the weaker was the interference of the incongruent cues. In contrast, interference increased with the level of loneliness in the HC group. - Conclusions - Behavioural mimicry was increased in BPD. However, this effect was less pronounced in those BPD patients who reported the highest levels of loneliness. Our findings emphasize that mimicry is a complex construct and only some of the involved processes are altered in BPD. Future studies must further disentangle the contribution of cognitive and social cognitive processes, address a potential causality in the link between loneliness and mimicry in BPD, and relate alterations of mimicry to interpersonal dysfunction during every-day life.